Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By uniformly dispersing sulfonic acid compounds on the surface of lithium transition metal composite oxides, the problem of low initial efficiency in non-aqueous electrolyte secondary batteries was solved, achieving efficient lithium-ion insertion and extraction, and improving the initial efficiency and capacity of the battery.
Patent Information
- Application Number
- CN202480032956.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-29
- Filing Date
- 2024-05-16
- Publication Date
- 2026-01-13
AI Technical Summary
There is still room for improvement in the initial efficiency of existing non-aqueous electrolyte secondary batteries, especially in the uniformity and distribution of sulfonic acid compounds on the surface of lithium transition metal composite oxides.
By uniformly dispersing sulfonic acid compounds on the surface of lithium transition metal composite oxides to achieve a Gini coefficient below 0.7 on the secondary particle cross section, the lithium ion insertion and extraction process is optimized. Lithium transition metal composite oxides are prepared using a specific process and sulfonic acid compounds are added to improve the initial efficiency.
It significantly improves the initial efficiency of non-aqueous electrolyte secondary batteries, enhances the lithium-ion insertion and extraction process, and improves the battery's capacity and performance.
Smart Images

Figure CN121336294A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. BACKGROUND
[0002] In recent years, the use of nonaqueous electrolyte secondary batteries has expanded to power sources for electric vehicles and / or power storage devices for efficient use of natural energy, and the like. The characteristics required of the positive electrode active material used in nonaqueous electrolyte secondary batteries also vary depending on the use. For example, Patent Literature 1 discloses a nonaqueous electrolyte secondary battery whose object is to reduce the reaction resistance at the time of storage at high temperatures, and as the positive electrode active material, a lithium transition metal complex oxide having a low-solubility Li salt dispersed on the surface is used.
[0003] PRIOR ART DOCUMENTS
[0004] PATENT LITERATURE
[0005] Patent Literature 1: Japanese Patent Application Publication No. 2019-169286 SUMMARY
[0006] In a nonaqueous electrolyte secondary battery, it is an important issue to improve the initial efficiency of charge and discharge. The technology described in Patent Literature 1 does not study the improvement of the initial efficiency, and there is room for improvement.
[0007] An object of the present disclosure is to provide a positive electrode active material for a nonaqueous electrolyte secondary battery that can improve the initial efficiency.
[0008] The positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure is characterized by containing: a lithium transition metal complex oxide, and a sulfonic acid compound present on the surface of the lithium transition metal complex oxide, the lithium transition metal complex oxide being secondary particles having a layered structure and containing 75 mol% or more of Ni with respect to the total number of moles of metal elements other than Li, in an element concentration distribution in the cross section of the secondary particles using a time-of-flight type secondary ion mass spectrometry, SO 3- The Gini coefficient on the surface of the secondary particles is 0.7 or less.
[0009]
[0010] (In the formula, A is a Group 1 element or a Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0011] The positive electrode active material for a nonaqueous electrolyte secondary battery according to another embodiment of the present disclosure is characterized by containing: a lithium transition metal complex oxide, and a sulfonic acid compound present on the surface of the lithium transition metal complex oxide, the lithium transition metal complex oxide being secondary particles having a layered structure and containing 75 mol% or more of Ni with respect to the total number of moles of metal elements other than Li, in an element concentration distribution in the cross section of the secondary particles using a time-of-flight type secondary ion mass spectrometry, SO 3- The Gini coefficient inside the secondary particles is 0.6 or less.
[0012]
[0013] (In the formula, A is a Group 1 element or a Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0014] The nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure is characterized by including a positive electrode containing the above-described positive electrode active material, a negative electrode, and a nonaqueous electrolyte, and the negative electrode contains S.
[0015] According to the positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, the initial efficiency of the nonaqueous electrolyte secondary battery can be improved. BRIEF DESCRIPTION OF DRAWINGS
[0016] Figure 1 is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery that is one example of an embodiment. DETAILED DESCRIPTION
[0017] As described above, in a nonaqueous electrolyte secondary battery, improving the initial efficiency is an important issue. The present inventors have found that, by causing a sulfonic acid compound to be present on the surface of a prescribed lithium transition metal oxide and causing the sulfonic acid compound to be uniformly dispersed up to the depth of SO 3- , the Gini coefficient of the depth mapping intensity ratio distribution of SO + becomes 0.7 or less, the protective effect of the coating film containing the sulfonic acid compound is significantly exerted, the insertion / extraction of Li
[0018] Hereinafter, one example of an embodiment of the nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail. In the following description, specific numerical values and / or materials, designs are sometimes exemplified, but other numerical values and / or materials, designs can also be applied as long as the effects of the present disclosure are obtained. Hereinafter, a cylindrical battery in which a wound electrode body is housed in a cylindrical exterior body will be exemplified, but the electrode body is not limited to the wound type, and can be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator. In addition, the exterior body is not limited to the cylindrical shape, and can be, for example, a square shape, a coin shape, or the like, or a battery case composed of a laminate sheet including a metal layer and a resin layer.
[0019] Figure 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as one example of an embodiment. As shown in Figure 1 , the secondary battery 10 is provided with a wound electrode body 14, an electrolyte, and an exterior body 16 that houses the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The exterior body 16 is a bottomed cylindrical metal container having an opening on one axial side, and the opening of the exterior body 16 is closed by a closure 17. Hereinafter, the closure 17 side of the battery will be referred to as the upper side, and the bottom side of the exterior body 16 will be referred to as the lower side for ease of description.
[0020] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode body 14 are each a long strip-shaped body having a rectangular shape, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape in the length direction. The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. In order to prevent precipitation of lithium, the negative electrode 12 is formed to have a size that is one turn larger than the positive electrode 11. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. Two separators 13 are formed to have a size that is at least one turn larger than the positive electrode 11, and are disposed, for example, in a manner of sandwiching the positive electrode 11. The electrode body 14 is provided with a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 is the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 is the axial direction. That is, the end surface in the width direction of the positive electrode 11 and the negative electrode 12 forms an end surface in the axial direction of the electrode body 14.
[0021] Insulating plates 18, 19 are disposed on the upper and lower sides of the electrode body 14, respectively. In Figure 1In the illustrated example, the positive electrode lead 20 extends to the side of the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the exterior body 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, i.e., the lid 27, which is electrically connected to the internal terminal plate 23, becomes a positive electrode terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the exterior body 16 by welding or the like, and the exterior body 16 becomes a negative electrode terminal.
[0022] A gasket 28 is provided between the exterior body 16 and the sealing body 17, and the airtightness of the inside of the battery can be ensured. A groove portion 22, in which a portion of the side surface portion of the exterior body 16 protrudes inward and supports the sealing body 17, is formed in the exterior body 16. The groove portion 22 is preferably formed in a ring shape along the circumferential direction of the exterior body 16, and supports the sealing body 17 with its upper surface. The sealing body 17 is fixed to the upper portion of the exterior body 16 by the groove portion 22 and the open end portion of the exterior body 16 which is fitted to the sealing body 17.
[0023] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a lid 27 are sequentially stacked from the side of the electrode body 14. Each member constituting the sealing body 17 has, for example, a circular plate shape or a ring shape, and each member other than the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected by respective central portions, and the insulating member 25 is interposed between each of the peripheral portions. When the internal pressure of the battery rises due to abnormal heat generation, the lower valve body 24 deforms to push the upper valve body 26 toward the lid 27 side and breaks, so that the current path between the lower valve body 24 and the upper valve body 26 is cut off. When the internal pressure further rises, the upper valve body 26 breaks, and gas is discharged from the opening portion of the lid 27.
[0024] Hereinafter, the positive electrode 11, the negative electrode 12, the separator 13, and the nonaqueous electrolyte constituting the secondary battery 10, and particularly the positive electrode 11, will be described in detail.
[0025] [Positive Electrode]
[0026] The positive electrode 11, for example, has a positive electrode core and a positive electrode additive layer formed on the surface of the positive electrode core. The positive electrode additive layer is preferably formed on both sides of the positive electrode core. For the positive electrode core, a metal foil stable within the potential range of the positive electrode 11, such as aluminum or an aluminum alloy, or a thin film formed by depositing this metal on the surface, can be used. The thickness of the positive electrode core is, for example, 10 μm or more and 30 μm or less. The positive electrode additive layer, for example, contains a positive electrode active material, a conductive agent, and a binder. The thickness of the positive electrode additive layer is, for example, 10 μm or more and 150 μm or less on one side of the positive electrode current collector. The positive electrode 11 can be manufactured, for example, by coating the surface of the positive electrode current collector with a positive electrode additive slurry containing a positive electrode active material, a conductive agent, and a binder, drying the coating, and then calendering it to form a positive electrode additive layer on both sides of the positive electrode current collector.
[0027] Examples of conductive agents included in the positive electrode binder layer include carbon-based materials such as acetylene black (AB), carbon black (CB) such as Ketjen black, carbon nanotubes (CNTs), graphene, and graphite. These can be used individually or in combination of two or more. The content of the conductive agent in the positive electrode binder layer relative to the total mass of the positive electrode binder layer is, for example, 0.1% by mass or more and 10% by mass or less.
[0028] Examples of binders included in the positive electrode binder layer include fluorinated resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These can be used individually or in combination of two or more. The binder content in the positive electrode binder layer is, for example, 0.1% by mass or more and 10% by mass or less relative to the total mass of the positive electrode binder layer.
[0029] The positive electrode active material contained in the positive electrode compound layer 31 comprises particulate lithium transition metal composite oxide. The lithium transition metal composite oxide particles include, for example, secondary particles formed by the aggregation of primary particles. The particle size of the primary particles is, for example, 0.02 μm or more and 2 μm or less. The particle size of the primary particles is determined as the diameter of the circumcircle in a particle image observed by a scanning electron microscope (SEM). The average particle size of the secondary particles is, for example, 2 μm or more and 30 μm or less. Here, the average particle size refers to the median particle size (D50) in a volumetric reference. D50 refers to the particle size at which the cumulative frequency in the volumetric particle size distribution reaches 50% from the smallest end, also known as the median diameter. The particle size distribution of the secondary particles can be measured using a laser diffraction-type particle size distribution measuring device (e.g., MicrotracBEL Co., Ltd., MT3000II) with water as the dispersion medium.
[0030] The lithium transition metal composite oxide particles include, for example, single particles or secondary particles composed of aggregates of two or more but less than 1000 single particles. The average particle size of the single particles is preferably 0.5 μm or more and 5 μm or less, more preferably 0.7 μm or more and 4 μm or less. It should be noted that single particles and secondary particles perform the same function; therefore, the term "secondary particles" below includes single particles.
[0031] Lithium transition metal composite oxides exhibit a layered structure. Examples of layered structures in lithium transition metal composite oxides include those belonging to space group R-3m and those belonging to space group C2 / m. From the viewpoints of high capacity and crystal structure stability, lithium transition metal composite oxides preferably possess a layered structure belonging to space group R-3m. The layered structure of lithium transition metal composite oxides may comprise a transition metal layer, a Li layer, and an oxygen layer.
[0032] The lithium transition metal composite oxide contains 75 mol% or more of Ni relative to the total molar percentage of metal elements other than Li. This enables high battery capacity. The Ni content is, for example, 80 mol% or more and 98 mol% or less. The lithium transition metal composite oxide may contain one or more elements selected from the group consisting of Co, Al, and Mn, in addition to Ni. The content of Co, Al, and Mn in the lithium transition metal composite oxide, relative to the total molar percentage of metal elements other than Li, is, for example, 0 mol% or more and 25 mol% or less, respectively. Furthermore, the combined content of Co, Al, and Mn is, for example, 0 mol% or more and 25 mol% or less.
[0033] Lithium transition metal composite oxides, for example, are of the general formula Li a Ni x M1 y M2 z O 2-b (Where, 0.8≤a≤1.2, 0.75≤x≤0.98, 0≤y≤0.25, 0≤z≤0.10, 0≤b≤0.05, x+y+z=1, M1 is one or more elements selected from the group consisting of Co, Al, and Mn, and M2 is one or more elements selected from the group consisting of Sr, Ca, Nb, Ti, Zr, and W) shows the composite oxide. The proportion of metal elements contained in the lithium transition metal composite oxide can be determined, for example, by inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0034] Lithium transition metal composite oxides are manufactured, for example, through the following steps: a first step, synthesizing a transition metal composite hydroxide containing Ni, Co, Mn, Al, etc. by co-precipitation; a second step, heat-treating the composite hydroxide to obtain a transition metal composite oxide; and a third step, mixing the composite oxide with lithium hydroxide and calcining it.
[0035] In the third step, the mixture is calcined at a temperature of 650°C or higher. The preferred range for the calcination temperature is 650°C or higher and 1100°C or lower. Calcination is preferably carried out in an oxygen stream. In the third step, from the viewpoint of discharge capacity, a lithium source (lithium hydroxide) in excess of the target product's stoichiometric ratio is used. For example, it is preferably 1 to 1.1 times the stoichiometric ratio of the composite oxide. Furthermore, by adjusting the calcination conditions, the particle size of the primary particles can be adjusted, and single particles can also be produced. For example, by increasing the maximum reaching temperature, the particle size of the single particles can be increased.
[0036] In addition to lithium transition metal complex oxides, the positive electrode active material also contains sulfonic acid compounds represented by general formula I. These sulfonic acid compounds are present on the surface of the lithium transition metal complex oxides.
[0037]
[0038] (In the formula, A is a group 1 or group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0039] In the elemental concentration distribution of secondary particle cross sections of lithium transition metal composite oxides analyzed using time-of-flight secondary ion mass spectrometry, SO 3- The Gini coefficient on the surface of the secondary particles can be 0.7 or less, preferably 0.6 or less, and more preferably 0.5 or less. This improves the initial efficiency. 3- SO was detected due to sulfonic acid compounds. 3- The smaller the Gini coefficient on the surface of secondary particles, the more uniformly the sulfonic acid compound is dispersed on the surface of the secondary particles. 3- The Gini coefficient on the surface of secondary particles is, for example, greater than 0.1.
[0040] In the elemental concentration distribution of secondary particle cross sections of lithium transition metal composite oxides analyzed using time-of-flight secondary ion mass spectrometry, SO 3- The Gini coefficient within the secondary particles can be 0.6 or less, preferably 0.55 or less, and more preferably 0.5 or less. This improves the initial efficiency. 3- SO was detected due to sulfonic acid compounds. 3- The smaller the Gini coefficient inside the secondary particles, the more uniformly the sulfonic acid compound is dispersed within the secondary particles. 3-The Gini coefficient inside the secondary particles is, for example, above 0.1.
[0041] SO 3- The Gini coefficient at the surface of secondary particles is the SO value for the surface of secondary particles. 3- Standardization strength I SO3-_OUT When expressing the cumulative rate in order of intensity, the value is twice the area enclosed between the diagonal and the Lorenz curve. 3- The Gini coefficient inside the secondary particle is relative to the SO inside the secondary particle. 3- Standardization strength I SO3-_IN The Gini coefficient, expressed in order of intensity as the cumulative rate, is twice the area enclosed by the diagonal and the Lorenz curve. The Gini coefficient is 0 in perfectly homogeneous conditions, and its value increases as homogeneity decreases. 3- The Gini coefficient inside secondary particles can be less than SO. 3- The Gini coefficient on the surface of secondary particles can also be SO. 3- Above the Gini coefficient on the surface of secondary particles. When SO 3- The Gini coefficient inside the secondary particles is SO. 3- When the Gini coefficient of the secondary particle surface is above a certain level, the effects of this application can sometimes be significantly enhanced.
[0042] SO 3- The normalized intensity ratio was obtained using a time-of-flight secondary ion mass spectrometer (IONTOF-SIMS5) and determined under the following conditions.
[0043] Primary ion: Bi3 +
[0044] Ionization voltage: 30kV
[0045] Ion current: 0.03pA@100us
[0046] Observation range: 50μm × 50μm
[0047] Quality range: 60µs (~310amu)
[0048] Detection: 4 frames / scan, 150 scans
[0049] The values obtained from the above measurements represent Ni and SO. 3- The concentration distribution image was segmented into 256×256 pixels, and the concentrations of Ni and SO were calculated for each pixel. 3- The detection intensity. Then, calculate SO. 3- The ratio of the detection intensity of SO to the detection intensity of Ni is used as SO. 3- Standardization strength I SO3- .
[0050] The area from the surface of the secondary particle identified in the above image to within 0.5 μm is defined as the surface of the secondary particle, and the pixels contained on the surface of this secondary particle (hereinafter referred to as surface pixels) are determined. I corresponds to each surface pixel. SO3- The set is I SO3-_OUT Furthermore, the inner part of the surface of the secondary particle, as determined above, is considered the interior of the secondary particle, and the pixels contained within this interior (hereinafter referred to as internal pixels) are determined. I corresponds to each internal pixel. SO3- The set is I SO3-_IN . byI SO3-_OUT and I SO3-_IN Calculate the SO on the surface of secondary particles 3- The Gini coefficient and SO inside secondary particles 3- The Gini coefficient. The specimens for cross-sectional observation can be specimens in which lithium transition metal composite oxides are embedded in resin or the like, or positive electrode composite layers containing lithium transition metal composite oxides.
[0051] In the above general formula I, A is preferably a group 1 element, and more preferably Li. This further reduces the DC resistance. It should be noted that when A is a group 1 element, n=1.
[0052] In general formula I, R is preferably an alkyl group. R is more preferably an alkyl group with 5 or fewer carbon atoms, even more preferably an alkyl group with 3 or fewer carbon atoms, and particularly preferably methyl. Furthermore, in R, some of the hydrogen atoms bonded to the carbon atoms can be replaced by fluorine. However, in R, not all the hydrogen atoms bonded to the carbon atoms are replaced by fluorine. The small molecular weight of R reduces DC resistance.
[0053] Examples of sulfonic acid compounds include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, magnesium methanesulfonate, and lithium fluoromethanesulfonate.
[0054] The amount of sulfonic acid compound contained in the cathode 11 is preferably 0.1% by mass or more and 1.5% by mass or less relative to the mass of the lithium transition metal composite oxide, more preferably 0.25% by mass or more and 1.0% by mass or less.
[0055] The presence of sulfonic acid compounds in cathode 11 can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, cathode 11 can be detected at 1238 cm⁻¹. -1 1175cm -1 1065cm -1 785cm -1 At least one nearby location has an absorption peak.
[0056] In the infrared absorption spectrum obtained by FT-IR, for example, the cathode 11 containing lithium methanesulfonate shows an absorption rate of 1238 cm⁻¹. -1 1175cm -1 1065cm -1 and 785cm -1 There is an absorption peak nearby. 1238cm -1 1175cm -1 1065cm -1 The nearby peak originates from the SO stretching vibration of lithium methanesulfonate. (785 cm⁻¹) -1 The nearby peaks are absorption peaks caused by the CS stretching vibration of lithium methanesulfonate.
[0057] In cathode 11 containing sulfonic acid compounds other than lithium methanesulfonate, absorption peaks from sulfonic acid compounds can be identified in the same way as in cathode 11 containing lithium methanesulfonate. It should be noted that the presence of sulfonic acid compounds in cathode 11 can also be confirmed by ICP, atomic absorption spectrometry, X-ray photoelectron spectroscopy (XPS), synchrotron radiation XRD, TOF-SIMS, etc.
[0058] Metal compounds can also exist on the surface of lithium transition metal complex oxides. These metal compounds contain one or more metallic elements selected from, for example, the group consisting of Sr, Ca, W, Zr, rare earth elements, and Al. Examples of Sr-containing compounds include SrO, Sr(OH)2, and / or SrCO3. Examples of Ca-containing compounds include CaO, Ca(OH)2, and / or CaCO3. Examples of W-containing compounds include WO3. Examples of Al-containing compounds include Al2O3. Examples of Zr-containing compounds include ZrO2, Zr(OH)4, Zr(CO3)2, and / or Zr(SO4)2·4H2O. Examples of rare earth-containing compounds include rare earth oxides, hydroxides, carbonates, sulfates, nitrates, and phosphates. Furthermore, the metal compound can contain multiple of these metallic elements, such as SrAlO4 and CaAlO4. The metal compound may further contain Li, such as lithium tungstate.
[0059] Nonmetallic compounds can also exist on the surface of lithium transition metal complex oxides. These nonmetallic compounds contain, for example, one or more nonmetallic elements selected from the group consisting of P and B. Li can be cited as an example of a compound containing P. 3- x H x PO4 (0≤x≤3). Examples of compounds containing B include H3BO3, Li3BO3, and Li2B4O7.
[0060] Positive electrode active materials can be produced, for example, by adding a sulfonic acid solution to a lithium transition metal composite oxide, causing the sulfonic acid compound to adhere to the surface of the lithium transition metal composite oxide (addition process). The lithium transition metal composite oxide can then undergo a cleaning process and a drying process.
[0061] In the cleaning process, the lithium transition metal composite oxide is washed with water and dehydrated to obtain a cake-like composition. Washing and dehydration can be performed using known methods and conditions. It is acceptable as long as the process does not degrade the battery characteristics due to lithium leaching from the lithium transition metal composite oxide. It should be noted that the positive electrode active material in this embodiment has low residual alkaline content because it has been washed with water.
[0062] In the drying process, the cake-like composition obtained in the washing process is dried to obtain a powdered composition. The drying process can be carried out under a vacuum atmosphere. The drying conditions are, for example, 150°C or higher and 400°C or lower, and 0.5 hours or higher and 15 hours or lower. A heat treatment can also be performed after the drying process. The heating temperature is, for example, 100°C to 450°C. This heat treatment can also be performed after the crushing process described later.
[0063] By crushing the powdery composition obtained in the drying process, individual particles can be obtained. Crushing can be performed using a grinding mill, etc. Crushing using a grinding mill can be carried out, for example, using a PJM-80 (manufactured by NPK, Japan) under the following conditions.
[0064] Compressed air consumption: 0.5 Nm 3 / minute
[0065] Supply gas pressure: 0.53 MPa
[0066] Processing capacity: 2000g / hour
[0067] In the addition step, at least one of a sulfonic acid compound and a sulfonic acid solution is added to the cake-like composition obtained in the cleaning step or the powder-like composition obtained in the drying step. This allows the sulfonic acid compound to adhere to the surface of the lithium transition metal complex oxide. Preferably, at least one of a sulfonic acid compound and a sulfonic acid solution is added to the cake-like composition. The sulfonic acid compound can be in either powder or solution form. The sulfonic acid solution is, for example, a methanesulfonic acid solution obtained by dissolving methanesulfonic acid in water. Since a Li compound remains in the cake-like composition, and this residual Li compound dissolves in the water contained in the cake-like composition, a Li-containing sulfonic acid compound is formed even when a sulfonic acid solution is added. From the viewpoint of more easily obtaining the effects of this application, the Li compound or Li compound solution can be added together with the sulfonic acid solution to the cake-like composition or the powder-like composition, or a mixed solution obtained by pre-mixing the sulfonic acid solution with the Li compound or Li compound solution can be added to the cake-like composition or the powder-like composition. The Li compound is, for example, LiOH, and the Li compound solution is, for example, a LiOH solution obtained by dissolving LiOH in water. The amounts of Li compound and sulfonic acid solution added to the cake-like composition preferably satisfy a molar ratio of 0 ≤ Li compound / sulfonic acid ≤ 1.3. The amount of sulfonic acid compound or sulfonic acid added relative to the mass of the lithium transition metal composite oxide is preferably 0.1% to 1% by mass, more preferably 0.3% to 0.8% by mass. The concentrations of the sulfonic acid solution and the sulfonic acid compound solution are, for example, 0.5% to 40% by mass. The addition process can be carried out during the cleaning process, after the cleaning process, during the drying process, or after the drying process, and the timing can be varied appropriately.
[0068] The dispersibility of sulfonic acid compounds on the surface and inside lithium transition metal composite oxides is improved by mixing them after adding at least one of a sulfonic acid compound and a sulfonic acid solution to the cake-like or powder-like composition. That is, by mixing, the SO₂ concentration can be reduced. 3- The Gini coefficient is measured on the surface and inside of the secondary particles. This mixing can be performed, for example, using a mixer at a speed of 10 rpm to 100 rpm for 0.1 minutes to 60 minutes.
[0069] By adding raw materials containing metal or non-metal compounds during, for example, the synthesis process, the synthesis process, the cleaning process, the cleaning process, the drying process, the drying process, or the addition process, it is possible to attach metal compounds containing one or more metal elements selected from the group consisting of Sr, Ca, W, Zr, rare earth elements, and Al, and non-metal compounds containing one or more non-metal elements selected from the group consisting of P and B, to the surface of lithium transition metal composite oxides. Examples of Sr raw materials include Sr(OH)₂, Sr(OH)₂•8H₂O, SrO, SrCo₃, SrSO₄, and Sr(NO₃). 2、 Examples of raw materials for calcium include SrCl2 and SrAlO4. Other examples include Ca(OH)2, CaO, CaCO3, CaSO4, and Ca(NO3). 2、 CaCl2, CaAlO4, etc. Examples of Zr raw materials include Zr(OH)4, ZrO2, Zr(CO3)2, Zr(SO4)2•4H2O, etc. Examples of rare earth raw materials include rare earth oxides, hydroxides, carbonates, etc. Examples of W raw materials include tungsten oxide (WO3), lithium tungstate (Li2WO4, Li4WO5, Li6W2O9), etc. It should be noted that solutions containing W can also be used as W raw materials. Additionally, Al raw materials can include Al2O3, Al(OH)3, Al2(SO4)3, etc., or Al derived from lithium transition metal complex oxides. Examples of P raw materials include Li. 3-x H x PO4 (0≤x≤3), etc. Examples of raw materials for B include H3BO3, Li3BO3, and Li2B4O7. These compounds can also be pulverized, with appropriate changes to the particle size or the amount of water, including hydrates, for use.
[0070] In addition to the positive electrode active material described in this embodiment, the positive electrode additive layer may also contain other positive electrode active materials. Examples of other positive electrode active materials include positive electrode active materials containing lithium transition metal composite oxides with a Ni content of less than 75 mol%, and positive electrode active materials in which sulfonic acid compounds are not present on the surface of lithium transition metal composite oxides.
[0071] [negative electrode]
[0072] The negative electrode 12 may, for example, have a negative electrode core body and a negative electrode mixture layer formed on the surface of the negative electrode core body, or a metal Li foil may be used as the negative electrode 12. In addition, the negative electrode 12 may have a negative electrode core body, and lithium metal may be deposited on the surface of the negative electrode core body during charging. When the negative electrode 12 has a negative electrode mixture layer, the negative electrode mixture layer is preferably formed on both sides of the negative electrode core body. The negative electrode core body may use a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode 12, a thin film having such a metal disposed on the surface layer, or the like. The thickness of the negative electrode core body is, for example, 5 μm or more and 30 μm or less. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The thickness of the negative electrode mixture layer is, for example, 10 μm or more and 150 μm or less on one side of the negative electrode core body. The negative electrode 12 can be produced, for example, by coating a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. on the surface of the negative electrode core body, drying the coating film, and then performing rolling to form a negative electrode mixture layer on both sides of the negative electrode core body.
[0073] As the negative electrode active material contained in the negative electrode mixture layer, there is no particular limitation as long as it is a material that can reversibly absorb and release lithium ions, and generally carbon materials such as graphite can be used. The graphite can be any of natural graphite such as flake graphite, massive graphite, and earthy graphite, massive artificial graphite, graphitized mesophase carbon microspheres, and other artificial graphite. In addition, as the negative electrode active material, metals alloyed with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. can also be used. In addition, materials provided with a carbon coating film for these can also be used. For example, a Si-containing compound represented by SiO x (0.5 ≤ x ≤ 1.6), or a Si-containing compound in which fine particles of Si are dispersed in a lithium silicate phase represented by Li 2y SiO (2+y) (0 < y < 2) can be used in combination with graphite.
[0074] Examples of the binder contained in the negative electrode mixture layer include styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts (which can be PAA-Na, PAA-K, etc., and also partially neutralized salts), polyvinyl alcohol (PVA), etc. These can be used alone or in combination of two or more.
[0075] The negative electrode 12 preferably contains sulfur (S). This further improves the initial efficiency. For example, by aging the secondary battery 10, a portion of the S contained in the positive electrode 11 can be moved to the negative electrode 12. The S content in the negative electrode 12, relative to the total mass of the negative electrode active material, is, for example, 10 ppm or more and 1000 ppm or less. The S content in the negative electrode 12 can be determined, for example, by using an ICP emission spectrometer (ICP-AES). The aging process can be carried out, for example, by charging at a constant current of 0.1C or more and 0.5C or less for 10 minutes or more and 60 minutes or less, followed by storage at a temperature of 40°C to 80°C for 10 to 20 hours.
[0076] [Separator]
[0077] The separator 13 can be a porous sheet with ion permeability and insulation. Specific examples of porous sheets include microporous films, woven fabrics, and nonwoven fabrics. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance, such as an aromatic polyamide resin, can be formed on the surface of the separator 13.
[0078] A filler layer containing inorganic filler can be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of inorganic fillers include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphoric acid compounds. The filler layer can be formed by coating a slurry containing the filler onto the surface of the positive electrode 11, the negative electrode 12, or the separator 13.
[0079] [Non-aqueous electrolytes]
[0080] Non-aqueous electrolytes, for example, have lithium-ion conductivity. Non-aqueous electrolytes can be liquid electrolytes (electrolytes) or solid electrolytes.
[0081] Liquid electrolytes (electrolytes) may include, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixtures of two or more of these solvents. The non-aqueous solvent may contain a halogen-substituted form, in which at least a portion of the hydrogen atoms of the solvent are replaced by halogen atoms such as fluorine. Examples of halogen-substituted forms include fluorocyclic carbonates such as fluoroethylene carbonate (FEC), fluorochain carbonates, and fluorochain carboxylic acid esters such as methyl fluoropropionate (FMP).
[0082] Examples of the aforementioned esters include: cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylic acid esters such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).
[0083] Examples of the aforementioned ethers include: 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-epoxybutane, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-eucalyptol, crown ethers and other cyclic ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, and dihexyl ether. Ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and other chain ethers.
[0084] The preferred electrolyte salt is a lithium salt. Examples of lithium salts include: LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, and LiB. 10 Cl 10Examples of lithium salts include lower aliphatic carboxylic acids such as lithium Cl, LiBr, LiI, phosphates, borates, and imide salts. Examples of phosphates include lithium difluorophosphate (LiPO₂F₂), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium tetrafluoro(oxalate)phosphate. Examples of borates include lithium bis(oxalate)borate (LiBOB) and lithium difluoro(oxalate)borate (LiDFOB). Examples of imide salts include lithium difluorosulfonylimide (LiN(FSO₂)₂), lithium bis(trifluoromethanesulfonate)imide (LiN(CF₃SO₂)₂), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF₃SO₂)(C₄F₉SO₂)), and lithium bis(pentafluoroethanesulfonate)imide (LiN(C₂F₅SO₂)₂). Among these, LiPF₆ is preferred from the perspectives of ionic conductivity and electrochemical stability. The concentration of lithium salt can be, for example, less than 4 moles per 1 L of non-aqueous solvent, less than 3 moles, preferably less than 1.8 moles, and more preferably more than 0.8 moles and less than 1.8 moles.
[0085] Non-aqueous electrolytes may contain additives. Examples of additives include unsaturated carbonates, acid anhydrides, phenolic compounds, benzene compounds, nitrile compounds, isocyanate compounds, sulpholactone compounds, sulfuric acid compounds, borate ester compounds, phosphate ester compounds, and phosphite ester compounds.
[0086] Examples of unsaturated cyclic carbonates include: vinylene carbonate, 4-methylvinylene carbonate, 4,5-dimethylvinylene carbonate, 4-ethylvinylene carbonate, 4,5-diethylvinylene carbonate, 4-propylvinylene carbonate, 4,5-dipropylvinylene carbonate, 4-phenylvinylene carbonate, 4,5-diphenylvinylene carbonate, vinyl ethylene carbonate, divinyl ethylene carbonate, etc. Unsaturated cyclic carbonates can be used alone or in combination of two or more. A portion of the hydrogen atoms in an unsaturated cyclic carbonate can be replaced by fluorine atoms. An anhydride can be an anhydrous product formed by the intermolecular condensation of multiple carboxylic acid molecules, preferably an anhydride of a polycarboxylic acid. Examples of anhydrides of polycarboxylic acids include: succinic anhydride, maleic anhydride, phthalic anhydride, etc.
[0087] Examples of phenolic compounds include phenol and hydroxytoluene. Examples of benzene compounds include fluorobenzene, hexafluorobenzene, and cyclohexylbenzene (CHB).
[0088] Examples of nitrile compounds include adiponitrile, heptanonitrile, propionitrile, and succinic anionylene. Examples of isocyanate compounds include methyl isocyanate (MIC), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), and methylcyclohexane diisocyanate (BIMCH). Examples of sulcolone compounds include propane sulcolone and propene sulcolone. Examples of sulfuric acid compounds include ethylene sulfate, ethylene sulfite, dimethyl sulfate, and lithium fluorosulfate. Examples of borate compounds include trimethyl borate and tris(trimethylsilyl)borate. Examples of phosphate compounds include trimethyl phosphate and tris(trimethylsilyl) phosphate. Examples of phosphite compounds include trimethyl phosphite and tris(trimethylsilyl) phosphite.
[0089] As a solid electrolyte, examples include solid or gel-like polymer electrolytes and inorganic solid electrolytes. As an inorganic solid electrolyte, materials known in all-solid-state lithium-ion secondary batteries (e.g., oxide-based solid electrolytes, sulfide-based solid electrolytes, halogen-based solid electrolytes, etc.) can be used. Polymer electrolytes may contain, for example, lithium salts and a matrix polymer, or non-aqueous solvents, lithium salts, and a matrix polymer. As a matrix polymer, for example, a polymer material that gels by absorbing non-aqueous solvents is used. Examples of polymer materials include fluoropolymers, acrylic resins, and polyether resins.
[0090] Example
[0091] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited to the following examples.
[0092] <Example 1-1>
[0093] [Preparation of positive electrode active material]
[0094] The nickel-cobalt-aluminum composite hydroxide ([Ni) obtained by co-precipitation method) 0.90 Co 0.05 Al 0.05 A composite oxide containing Ni, Co, and Al was synthesized by calcining (OH)₂ at 500°C for 8 hours. This composite oxide was then mixed with LiOH at a molar ratio of 1:1.02, and the mixture was calcined at 800°C for 3 hours under an oxygen flow to obtain a lithium transition metal composite oxide. The lithium transition metal composite oxide is a secondary particle formed by the aggregation of primary particles.
[0095] In the aforementioned lithium transition metal composite oxide, water was added to a slurry concentration of 1500 g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition (washing step). Powdered lithium methanesulfonate was added to this cake-like composition and mixed for 10 minutes at 25 rpm using a mixer (PRIMIX, TKHIVIS MIX) (addition step). The amount of lithium methanesulfonate added was 0.5% by mass relative to the total mass of the lithium transition metal composite oxide. After the addition step, a drying process was performed under vacuum at 180°C for 2 hours to obtain the positive electrode active material of Example 1. The presence of lithium methanesulfonate on the surface of the positive electrode active material was confirmed using Fourier transform infrared spectroscopy (FT-IR). The elemental concentration distribution of the cross-section of the positive electrode active material was determined by time-of-flight secondary ion mass spectrometry (TOF-SIMS), and the results showed SO 3- The Gini coefficients on the surface and inside the secondary particles are 0.39 and 0.52, respectively. Furthermore, the results of the positive electrode active material determination using an ICP emission spectrometer (ICP-AES) confirmed the elements other than Li and O as shown in Table 1 (described later).
[0096] [The production of the positive electrode]
[0097] 92 parts by weight of the above-mentioned positive electrode active material, 5 parts by weight of acetylene black (AB), and 3 parts by weight of polyvinylidene fluoride (PVDF) were mixed, and N-methyl-2-pyrrolidone (NMP) was added in appropriate amount to prepare a positive electrode slurry. Next, the positive electrode slurry was coated onto both sides of a positive electrode core made of aluminum foil. After the coating was dried, it was calendered using calendering rollers and cut into specified electrode sizes to manufacture the positive electrode. It should be noted that an exposed portion of the positive electrode is provided, protruding from the surface of the positive electrode core.
[0098] [Making the negative electrode]
[0099] Natural graphite was used as the negative electrode active material. A negative electrode slurry was prepared by mixing the negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and lithium methanesulfonate in an aqueous solution at a solid content mass ratio of 100:1:1:0.08. The negative electrode slurry was then coated onto both sides of a negative electrode core made of copper foil. After drying, the coating was calendered using calendering rollers and cut into specified electrode sizes to fabricate the negative electrode. It should be noted that an exposed portion of the negative electrode was provided, protruding from the surface of the negative electrode core. The sulfur (S) content in the negative electrode was determined using an ICP-AES spectrometer, and the result was 250 ppm relative to the total mass of the negative electrode active material.
[0100] [Preparation of non-aqueous electrolytes]
[0101] A non-aqueous electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.2 mol / L in a mixed solvent consisting of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4.
[0102] [Fabrication of the Experimental Battery Cell]
[0103] A positive electrode lead is installed on the exposed portion of the positive electrode, and a negative electrode lead is installed on the exposed portion of the negative electrode. The positive and negative electrodes are wound into a spiral shape, sandwiched between a polyolefin separator, and then radially pressed to form a flat, wound electrode body. This electrode body is then housed in an outer casing made of aluminum laminate, and the aforementioned non-aqueous electrolyte is injected. The opening of the outer casing is then sealed to obtain the experimental battery cell.
[0104] [Evaluation of initial efficiency]
[0105] The test battery cells were charged at a constant current of 0.2C at 25°C until the battery voltage reached 4.2V. Then, they were charged at a constant voltage of 4.2V until the current reached 0.02C. After resting for 1 hour, they were discharged at a constant current of 0.2C until the battery voltage reached 2.5V. The initial efficiency was calculated using the following formula from the charging and discharging capacities measured during the above charging and discharging processes.
[0106] Initial efficiency = Discharge capacity / Charge capacity
[0107] <Examples 1-2>
[0108] In the preparation of the positive electrode active material, the mixing time of the cake composition and the powdered lithium methanesulfonate was changed to 3 minutes. Otherwise, the test battery cells were prepared and evaluated in the same manner as in Example 1-1.
[0109] <Examples 1-3~1-6>
[0110] In the preparation of the positive electrode active material, a lithium methanesulfonate solution dissolved in pure water was added instead of powdered lithium methanesulfonate. The amount of lithium methanesulfonate added and the mixing time of the cake-shaped composition and the powdered lithium methanesulfonate were varied as shown in Table 1. Otherwise, the test battery cells were prepared and evaluated in the same manner as in Examples 1-1. Fourier transform infrared spectroscopy (FT-IR) confirmed the presence of lithium methanesulfonate on the surface of each positive electrode active material.
[0111] <Examples 1-7>
[0112] In the process of adding the positive electrode active material, a solution containing methanesulfonic acid and LiOH dissolved in pure water at a molar ratio of 1:1 (hereinafter, methanesulfonic acid + LiOH solution) was added instead of powdered lithium methanesulfonate. The amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium transition metal composite oxide. Otherwise, test battery cells were fabricated and evaluated in the same manner as in Examples 1-1. It should be noted that the concentration of the added methanesulfonic acid + LiOH solution was 10% by mass, and the amount of lithium methanesulfonate added was as described above. The presence of lithium methanesulfonate on the surface of the positive electrode active material was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0113] <Examples 1-8>
[0114] In the process of adding the positive electrode active material, a solution containing methanesulfonic acid and LiOH dissolved in pure water at a molar ratio of 1:1 (hereinafter, methanesulfonic acid + LiOH solution) was added instead of powdered lithium methanesulfonate. The amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium transition metal composite oxide. Otherwise, test battery cells were fabricated and evaluated in the same manner as in Examples 1-2. It should be noted that the concentration of the added methanesulfonic acid + LiOH solution was 10% by mass, and the amount of lithium methanesulfonate added was as described above. The presence of lithium methanesulfonate on the surface of the positive electrode active material was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0115] <Examples 1-9>
[0116] After fabricating the test battery cells in the same manner as in Examples 1-3, they were subjected to aging treatment and their initial efficiency was evaluated as follows. From the negative electrode contained in the evaluated test battery cells, sulfur (S) of 250 ppm relative to the total mass of the negative electrode active material was detected.
[0117] [Evaluation of initial efficiency during aging treatment]
[0118] The test battery cells were charged at 0.2C for 30 minutes at 25°C, and then stored at 60°C for 15 hours. Next, the battery cells were charged again at a constant current of 0.2C at 25°C until the battery voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.02C. After resting for 1 hour, the batteries were discharged at a constant current of 0.2C until the battery voltage reached 2.5V. The initial efficiency was calculated from the charging and discharging capacities measured during the above charging and discharging processes using the following formula. It should be noted that the charging capacity is the sum of the capacity after charging at 0.2C for 30 minutes, the capacity after charging at 0.2C to 4.2V, and the capacity after charging at 4.2V to 0.02C.
[0119] Initial efficiency = Discharge capacity / Charge capacity
[0120] <Examples 1-10>
[0121] After fabricating the test battery cells in the same manner as in Examples 1-4, they underwent aging treatment and their initial efficiency was evaluated in the same manner as in Examples 1-9. From the negative electrode contained in the evaluated test battery cells, sulfur (S) of 400 ppm relative to the total mass of the negative electrode active material was detected.
[0122] <Comparative Example 1-1>
[0123] In the preparation of the positive electrode active material, the mixture of the cake-shaped composition and powdered lithium methanesulfonate was not performed. Otherwise, the test battery cells were prepared in the same manner as in Examples 1-1, and then aged and evaluated for initial efficiency in the same manner as in Examples 1-9. From the negative electrode contained in the evaluated test battery cells, sulfur (S) of 400 ppm relative to the total mass of the negative electrode active material was detected.
[0124] <Comparative Examples 1-2>
[0125] In the preparation of the positive electrode active material, the cake-shaped composition was not mixed with the powdered lithium methanesulfonate. Otherwise, the test battery cells were prepared and evaluated in the same manner as in Examples 1-1.
[0126] <Example 2-1>
[0127] [Preparation of positive electrode active material]
[0128] The nickel-manganese composite hydroxide ([Ni) obtained by co-precipitation method) 0.80 Mn 0.20A composite oxide containing Ni and Mn was synthesized by calcining (OH)2) at 500°C for 8 hours. This composite oxide was then mixed with LiOH at a molar ratio of 1:1.02, and the mixture was calcined at 900°C for 10 hours under an oxygen flow to obtain a lithium transition metal composite oxide. The lithium transition metal composite oxide was in the form of single particles.
[0129] In the aforementioned lithium transition metal composite oxide, water was added to a slurry concentration of 1500 g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition (washing step). A lithium methanesulfonate solution dissolved in pure water was added to this cake-like composition, and the mixture was stirred at 25 rpm for 10 minutes using a mixer (PRIMIX, TKHIVIS MIX) (addition step). The amount of lithium methanesulfonate solution added was 0.25% by mass relative to the total mass of the lithium transition metal composite oxide. After the addition step, a drying process was performed under vacuum at 180°C for 2 hours to obtain the positive electrode active material of Example 2-1. The presence of lithium methanesulfonate on the surface of the positive electrode active material was confirmed using Fourier transform infrared spectroscopy (FT-IR). The elemental concentration distribution of the cross-section of the positive electrode active material was determined by time-of-flight secondary ion mass spectrometry (TOF-SIMS), and the results showed SO₄²⁻¹. 3- The Gini coefficient on the surface of the positive electrode active material is 0.39. Furthermore, the results of ICP emission spectroscopy analysis of the positive electrode active material, excluding Li and O, confirmed the elements listed in Table 2.
[0130] Using the positive electrode active material of Example 2-1, test battery cells were fabricated and evaluated in the same manner as in Example 1-1.
[0131] <Examples 2-2~2-4>
[0132] In the preparation of the positive electrode active material, the amount of lithium methanesulfonate solution added and the mixing time of the cake composition and the lithium methanesulfonate solution were varied as shown in Table 1. Otherwise, the test battery cells were prepared and evaluated in the same manner as in Example 2-1. Fourier transform infrared spectroscopy (FT-IR) confirmed the presence of lithium methanesulfonate on the surface of each positive electrode active material.
[0133] <Comparative Example 2-1>
[0134] In the process of adding positive electrode active material, powdered lithium methanesulfonate is added instead of lithium methanesulfonate solution dissolved in pure water, and the cake composition is not mixed with powdered lithium methanesulfonate. Otherwise, test battery cells are made and evaluated in the same manner as in Example 2-1.
[0135] The evaluation results of the test battery cells of the Examples and Comparative Examples are shown in Tables 1 and 2. In Table 1, the initial efficiencies of the test battery cells of Examples 1-1 to 1-10 and Comparative Example 1-1 are expressed relative to the initial efficiency of the test battery cell of Comparative Example 1-2, which is set to 100. Similarly, in Table 2, the initial efficiencies of the test battery cells of Examples 2-1 to 2-4 are expressed relative to the initial efficiency of the test battery cell of Comparative Example 2-1, which is set to 100. Additionally, SO is also shown in Tables 1 and 2. 3- The Gini coefficient on the surface and inside of the lithium transition metal composite oxide particles, as well as the amount of lithium methanesulfonate added and the mixing time. It should be noted that S was not detected from the negative electrode of the test battery cells other than Examples 1-9, 1-10 and Comparative Example 1-1.
[0136] [Table 1]
[0137]
[0138] [Table 2]
[0139]
[0140] In Tables 1 and 2, the initial efficiency of the test cell cells in the examples is improved compared to the corresponding comparative example test cell cells. This tendency is particularly pronounced in the test cell cells that underwent aging treatment. Therefore, it can be seen that by presenting the sulfonic acid compound on the surface of a specified lithium transition metal oxide particle and uniformly dispersing the sulfonic acid compound until SO₂ is obtained during TOF-SIMS analysis, the efficiency is significantly improved. 3- The depth mapping intensity ratio distribution has a Gini coefficient of less than 0.7, thus improving the initial efficiency.
[0141] This disclosure is further illustrated by the following embodiments.
[0142] Option 1:
[0143] A positive electrode active material for a non-aqueous electrolyte secondary battery comprises: a lithium transition metal complex oxide and a sulfonic acid compound present on the surface of the lithium transition metal complex oxide.
[0144] The lithium transition metal composite oxide is a secondary particle with a layered structure and containing more than 75 mol% Ni relative to the total molar number of metal elements other than Li.
[0145] In the elemental concentration distribution of the secondary particle cross section using time-of-flight secondary ion mass spectrometry.
[0146] SO 3- The Gini coefficient on the surface of the secondary particles is below 0.7.
[0147]
[0148] (In the formula, A is a group 1 or group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0149] Option 2:
[0150] A positive electrode active material for a non-aqueous electrolyte secondary battery comprises: a lithium transition metal complex oxide and a sulfonic acid compound present on the surface of the lithium transition metal complex oxide.
[0151] The lithium transition metal composite oxide is a secondary particle with a layered structure and containing more than 75 mol% Ni relative to the total molar number of metal elements other than Li.
[0152] In the elemental concentration distribution of the secondary particle cross section using time-of-flight secondary ion mass spectrometry.
[0153] SO 3- The Gini coefficient inside the secondary particles is below 0.6.
[0154]
[0155] (In the formula, A is a group 1 or group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0156] Option 3:
[0157] According to Scheme 1 or 2, the positive electrode active material for a non-aqueous electrolyte secondary battery, wherein A is a group 1 element.
[0158] Option 4:
[0159] According to Scheme 1 or 2, the positive electrode active material for a non-aqueous electrolyte secondary battery, wherein A is Li.
[0160] Option 5:
[0161] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Schemes 1 to 4, wherein R is an alkyl group.
[0162] Option 6:
[0163] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Schemes 1 to 4, wherein R is methyl.
[0164] Option 7:
[0165] According to any one of Schemes 1 to 6, the amount of the sulfonic acid compound present on the surface of the lithium transition metal composite oxide is 0.1% by mass or more and 1.5% by mass or less relative to the mass of the lithium transition metal composite oxide.
[0166] Option 8:
[0167] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Schemes 1 to 7, wherein, in the infrared absorption spectrum, at 1238 cm⁻¹... -1 1175cm -1 1065cm -1 785cm -1 At least one nearby location has an absorption peak.
[0168] Option 9:
[0169] A non-aqueous electrolyte secondary battery comprises: a positive electrode, a negative electrode, and a non-aqueous electrolyte, all comprising the positive electrode active material for a non-aqueous electrolyte secondary battery as described in any one of claims 1 to 8.
[0170] The negative electrode contains sulfur (S).
[0171] Explanation of reference numerals in the attached figures
[0172] 10 Secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer body, 17 Sealing body, 18, 19 Insulating plate, 20 Positive lead, 21 Negative lead, 22 Groove, 23 Internal terminal block, 24 Lower valve body, 25 Insulating component, 26 Upper valve body, 27 Cover, 28 Gasket.
Claims
1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: a lithium transition metal complex oxide and a sulfonic acid compound present on the surface of the lithium transition metal complex oxide. The lithium transition metal composite oxide is a secondary particle with a layered structure and containing more than 75 mol% Ni relative to the total molar number of metal elements other than Li. In the elemental concentration distribution of the secondary particle cross section using time-of-flight secondary ion mass spectrometry. SO 3- The Gini coefficient on the surface of the secondary particles is below 0.
7. In the formula, A is a group 1 element or a group 2 element, R is a hydrocarbon group, and n is 1 or 2.
2. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: a lithium transition metal complex oxide and a sulfonic acid compound present on the surface of the lithium transition metal complex oxide. The lithium transition metal composite oxide is a secondary particle with a layered structure and containing more than 75 mol% Ni relative to the total molar number of metal elements other than Li. In the elemental concentration distribution of the secondary particle cross section using time-of-flight secondary ion mass spectrometry. SO 3- The Gini coefficient inside the secondary particles is below 0.
6. In the formula, A is a group 1 element or a group 2 element, R is a hydrocarbon group, and n is 1 or 2.
3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, A is a group 1 element.
4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, A is Li.
5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, R is an alkyl group.
6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, R is a methyl group.
7. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, The amount of the sulfonic acid compound present on the surface of the lithium transition metal composite oxide is more than 0.1% by mass and less than 1.5% by mass relative to the mass of the lithium transition metal composite oxide.
8. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, In the infrared absorption spectrum, at 1238 cm⁻¹ -1 1175cm -1 1065cm -1 785cm -1 At least one nearby location has an absorption peak.
9. A non-aqueous electrolyte secondary battery, comprising: a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery as described in claim 1 or 2, a negative electrode, and a non-aqueous electrolyte. The negative electrode contains sulfur (S).
Citation Information
Patent Citations
Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
JP2019169286A